Mongolia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2008)
The vast mineral deposits of Mongolia, if properly managed, could make available large budgetary resources, which would help address a wide range of its economic challenges. This report focuses on Mongolia's selected issues in the mining sector, government employment and wages, and saving and credit cooperatives. The attractiveness of Mongolia's mining sector has been eroded in recent years with the introduction of the windfall profit tax (WPT). The high wage bill mainly reflects the large size of government employment and the recent rapid real wage increases.